Endoscopic submucosal dissection with a novel high viscosity injection solution (LiftUp) in an ex vivo model: a prospective randomized study - Wedi, E.; Koehler, P.; Hochberger, J.; Maiss, J.; Milenovic, S.; Gromski, M.; Ho, N.; Gabor, C.; Baulain, U.; Ellenrieder, V.; Jung, C. (Endoscopy International Open, 2019)
Introduction Endoscopic submucosal dissection (ESD) is increasingly being used in the western world. Submucosal injectates are an essential tool for the ESD procedure. In this study, we evaluated a novel copolymer injectate (LiftUp, Ovesco, Tübingen Germany) in an established ESD model (EASIE-R) in comparison to existing submucosal injectables. Materials and methods We conducted a prospective, randomized ex vivo study performing ESD with three injectates: LiftUp, hydroxyethyl starch (HAES 6 %) and normal saline solution (NaCl 0.9 %). A total of 60 artificial lesions, each 3 × 3 cm in size, were resected in an ex vivo porcine model, utilizing one of the three studied injectates (n = 20 ESDs per injectate). Study parameters were: en bloc resection rate, perforation rate, lifting property, time of injection, injectate volume, general ESD procedure time, and overall procedure time. Results All 60 lesions were successfully resected using the standard ESD technique. LiftUp had no procedure related perforations, one perforation occurred in the HAES group, and two perforations in the NaCl group (P > 0.05). Furthermore, adequate lifting was achieved in 16/20 (80 %) using LiftUp, 6/20 (30 %) in the HAES group and 6/20 (30 %) in the NaCl group (P < 0.0002). En bloc resection was achieved in 19 (95 %) with LiftUp, in 20 (100 %) with HAES, and in 16 (80 %) with NaCl. General ESD procedure time and overall procedure time were not different among the three groups. Conclusion LiftUp appears to be a safe alternative to established fluids for ESD. It had a significantly improved lifting effect and required significantly less injected volume compared to well-established lifting solutions.